LABELING OF MIBI (METOXY ISOBUTYL ISONITRYL) WITH TECHNETIUM-99m AS A PERFUSION MYOCARDIAC IMAGING RADIOPHARMACEUTICAL - Nurlaila Z. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Coronary artery disease is one the major causes of death in Indonesia. For early diagnosis of the disease, it is deemed necessary to visualize the myocardium blood flow perfusion. 99mTc-MIBI labeled compound is one of the agent that could be used for such purpose. The labeling of MIBI with technetium-99m under some variations of several parameters has been carried out. The labeling efficiency was determined by counting the radiochemical purity using ITLC-SG 60 thin layer chromatography using two kinds of solvents, i.e. methanol and 0.9% NaCl solutions. The optimum labeling condition was achieved at the pH = 5.5 – 6.0, 1 mg of [Cu(MIBI)4BF4, 0.060 mg SnCl2.2H2O and 10 minutes incubation time in a boiling water bath, gave ± 99% of labeling efficiency. Under the formulation stated above, MIBI dry kit produces could give the radiochemical purity of more than 95%.Key words : metoxy isobutyl isonitril (MIBI), technetium-99m, labeling, myocardiac perfusion imaging.